Vol 2 no 2 Tahun 2024 PROGRAM ARISAN WISATA MENURUT PERSPEKTIF EKONOMI SYARIAH: STUDI KASUS DI KSPPS BISMILLAH CABANG NGADIREJO KABUPATEN TEMANGGUNG - tantowi, ahmad (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2024)
The tourism savings program, often referred to as a tourism fund, is one of the programs used by savings and loan cooperatives, including KSPPS Bismillah. This thesis discusses the tourism savings program from the perspective of Islamic economics at KSPPS Bismillah branch in Ngadirejo, Temanggung Regency. In this travel program, customers make monthly deposits in predetermined amounts and times and receive a bonus of a free trip. In this program, the contract used is the wadiah yad dhamanah, which is a deposit agreement for goods or money where the receiving party can utilize the deposited goods or money and is responsible for any loss or damage to those items. In return, the receiving party may provide a bonus incentive to the depositor. This practice certainly piqued the author's interest to delve deeper into the bonus practices on tourism savings and the perspective according to Islamic economic principles, as well as Fatwa DSN No:02/DSN-MUI/VI/2000 regarding wadi’ah savings. The purpose of this research is to determine and answer the question of whether the practice of the tourism savings program at KSPPS Bismillah is in accordance with Sharia, where KSPPS Bismillah is a Sharia savings and loan cooperative and financing institution. This type of research is field research. (field reseacrh). The primary data source in this research is interviews with the KSPPS Bismillah party. Meanwhile, the secondary data is obtained from the DSN-MUI fatwa, books, and previous research related to wadi’ah yad adh-dhamanah. In data collection, the author used observation, interviews, and documentation methods. After the data has been collected, the next step is to analyze the data. The data analysis technique that the author uses is qualitative descriptive method. Based on the research findings, it can be concluded that the savings product for tourism under the wadiah yad dhamanah contract practiced by KSPPS Bismillah Branch Ngadirejo, Temanggung Regency, has fulfilled the pillars and requirements of wadiah yad dhamanah and is in accordance with the Quran and Hadith. The granting of bonuses in this program is in accordance with Sharia law because, according to the DSN fatwa No. 86/DSN-MUI/XII/2012, the bonuses provided are in the form of free travel services rather than cash or goods. Furthermore, the practice aligns with the DSN fatwa No. 02/DSN-MUI/IV/2000, as the savings products that comply with Sharia use the mudharabah and wadiah contracts.